A Cross-Regional Study of ESG Strategies : IKEA vs. Home Depot - Šulcová, Adéla (2025)
This thesis presents a comparative analysis of the ESG strategies employed by IKEA and The Home Depot, two major global retailers operating in the home furnishings and home improvement sectors. The study examines how regional regulations, market conditions, and cultural norms in Europe and the United States shape corporate sustainability strategies, reporting practices, and overall ESG performance. The methodology combines quantitative analysis of environmental, social, and governance indicators with a qualitative review of corporate sustainability reports, regulatory frameworks, and relevant academic literature.